A MORPHO-SYNTACTIC ERROR ANALYSIS OF UNIVERSITY STUDENTS’ ARGUMENTATIVE WRITING - Hana Dhiya Ulhaq; Yayan Suryana; Nida Amalia Asikin; Fahrus Zaman Fadhly (Indonesian Journal of Learning and Instruction, 2022)
The research aims are to identify the morpho-syntactic errors in argumentative text writing by university students at the English Department of Kuningan University and find out the difficulties that students face in writing argumentative texts. A descriptive qualitative is used through the instruments of document analysis and interviews. The subject of this research was 5 students of the English Education Department who were in the second semester. The result of the document analysis showed that the errors in using prepositions as the most frequent error at 6 errors (25.24%), errors in using verbs group at 4 errors (16.5%), the third place of errors are errors in using articles and errors in word order, and errors in using relative clauses and relative pronouns for 3 errors (12.5%), errors in using tenses and errors in using adverbs for 2 errors (8.3%), the next is errors due to lack of concord for 1 error (4.16%) and the last is errors in using conditional sentences for 0 error. Moreover, the difficulties that students face in writing argumentative texts based on interviews were: language features, grammar, vocabulary election, writing strategy, personality background, study background, and the environment including learning sources. The errors were found in writing argumentative texts because these factors affected the student's performance in writing argumentative texts.Keywords: argumentative text; error analysis; morpho-syntax.